Effects of enhanced STI partner notification counselling and provider-assisted partner services on partner referral and the incidence of STI diagnosis in Cape Town, South Africa: randomised controlled trial. Issue 1 (1st June 2020) - Mathews, Catherine; Lombard, Carl; Kalichman, Moira; Dewing, Sarah; Banas, Ellen; Dumile, Sekelwa; Mdlikiva, Amanda; Mdlikiva, Thembinkosi; Jennings, Karen Ann; Daniels, Johann; Berteler, Marcel; Kalichman, Seth C
Abstract : Objectives: We investigated the effects of an enhanced partner notification (PN) counselling intervention with the offer of provider-assisted referral among people diagnosed with STI in a Cape Town public clinic. Methods: Participants were adults diagnosed with STI at a community clinic. After the standard STI consultation, participants were randomly allocated in a 1:1:1 ratio to (1) 'HE': 20 min health education; (2) 'RR': 45 min risk reduction skills counselling; or (3) 'ePN': 45 min enhanced partner notification communication skills counselling and the offer of provider-assisted referral. The primary outcome was the incidence of repeat STI diagnoses during the 12 months after recruitment, and the secondary outcome was participants' reports 2 weeks after diagnosis of notifying recent partners. Incidence rate ratios (IRRs) were used to compare the incidence rates between arms using a Poisson regression model. Results: The sample included 1050 participants, 350 per group, diagnosed with STI between June 2014 and August 2017. We reviewed 1048 (99%) participant records, and identified 136 repeat STI diagnoses in the ePN arm, 138 in the RR arm and 141 in the HE arm. There was no difference in the annual incidence of STI diagnosis between the ePN and HE arms (IRR: 1.0; 95% CI 0.7 to 1.3), or between the RR and HE arms (IRR: 0.9; 95% CI 0.7 to 1.2). There was a greater chance of a partner being notified in the ePN condition compared with the HE condition, 64.3% compared with 53.8%, but no difference between the RR and HE arms. Conclusions: PN counselling and education with provider-assisted services has the potential to change the behaviour of people diagnosed with STIs, increasing the number of partners they notify by more than 10%. However, these changes in behaviour did not lead to a reduction of repeat STI diagnoses. Trial registration number: PACTR201606001682364.